2016
DOI: 10.1080/07448481.2016.1269771
|View full text |Cite
|
Sign up to set email alerts
|

Using the Theory of Planned Behavior to predict HPV vaccination intentions of college men

Abstract: Practitioners may utilize this instrument for the development and evaluation of TPB-based interventions to increase HPV vaccination intentions of undergraduate college men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 29 publications
5
92
0
Order By: Relevance
“…Sexual health demographic variables such as participant's number of sexual partners, history of contracting an STI, and condom use highlighted emerging risk factors among this population; such findings are not uncommon, especially among this age group. 24 In an Irish study, from a total of 2784 first time STI clinic patients, aged [13][14][15][16][17][18][19] years, 1172 were diagnosed with a notifiable STI between January 1999 and September 2009. 25 Dominant risk factors associated with STI diagnosis included men who sometimes or never use condoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sexual health demographic variables such as participant's number of sexual partners, history of contracting an STI, and condom use highlighted emerging risk factors among this population; such findings are not uncommon, especially among this age group. 24 In an Irish study, from a total of 2784 first time STI clinic patients, aged [13][14][15][16][17][18][19] years, 1172 were diagnosed with a notifiable STI between January 1999 and September 2009. 25 Dominant risk factors associated with STI diagnosis included men who sometimes or never use condoms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several behavior‐specific meta‐analyses support the effectiveness of the TPB in condom use . The TPB has also been successfully applied to studies exploring male behaviors regarding HPV vaccination uptake …”
Section: Methodsologymentioning
confidence: 99%
See 1 more Smart Citation
“…TPB is widely used in different areas, including psychology (e.g., Hashim, Jawis, Wahat, and Grove 2014;Williamson, and Lawson 2015;Lheureux, Auzoult, Charlois, Hardy-Massard, and Minary 2016), biology (e.g., Sagas, Cunningham, and Pastore 2006;Hamilton, Cox, and White 2012), and for therapeutic use in the health sciences (e.g., Agarwal 2014;Catalano, Knowlden, Birch, Leeper, Paschal, and Usdan 2017). It remains the most commonly used predictive model to analyze human intentions today (Krueger Jr 2017).…”
Section: Theory Of Planned Behavior and Entrepreneurial Event Modelmentioning
confidence: 99%
“…6 The theory of planned behaviour (TPB) thinks that the intention is predicted by the positive attitudes toward a specific behaviour, the approval of the other significant subjective norms and a perceived behavioural control. 7 The TPB has been shown to predict the intention to adopt various health behaviours in both its original or modified versions, including the intention to vaccination. 8,9 Furthermore, Schmid suggested that the TPB could be further increased by integrating the concepts of risk perception, past behaviour, knowledge, and experience into the model when they reviewed the barriers of the influenza vaccination intention and behavior.…”
Section: Introductionmentioning
confidence: 99%